Persamaan Tujuan Implementasi Kurikulum Medeka dengan Pemikiran Al-Farabi dari Pendidikan Agama Islam - Al Hasan, Ahmad Rozik; Ratri, Rose Kusumaning (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
There is a lack of discussion about Al-Farabi's thoughts and many educators do not yet understand the objectives of the Independent Curriculum. The research objectives are: (1) To find out the objectives of implementing the independent curriculum and the objectives of Al-Farabi's thoughts from Islamic Religious Education. (2) To find out the similarities between the objectives of implementing the Independent Curriculum and Al-Farabi's Thoughts from Islamic Religious Education. In this research, the author uses the library research method, where the data to support the research is not directly confronted by empirical events or eyewitnesses but rather data produced by texts, articles, books, and so on. Therefore, in researching the aims of Al-Farabi's thoughts on Islamic religious education, the author uses assistance in the form of his own books and supporting books to become the basis for arguments that strengthen Al-Farabi's own thoughts. Based on the research results, it can be concluded that (1). Al-Farabi regarding the purpose of education: The purpose of education is to guide every individual towards the perfection of life. The perfect human (insan kamil) has theoretical goodness, intellectual knowledge, and practical morals and the application of practical morals in everyday life is emphasized. Objectives of Implementing the Merdek Curriculum: Aims at realizing meaningful and effective learning, Focuses on increasing faith, devotion to God Almighty, and noble morals, Emphasizes the development of students' creativity, taste and initiative as lifelong students with Pancasila character, Pancasila student profile prepared by considering global changes and national interests related to national culture, nationalism and the national development agenda, this curriculum is based on the mandate of the 1945 Constitution and Pancasila. (2) The similarity between the objectives of implementing the Merdeka Curriculum and Al-Farabi's thoughts on Islamic Religious Education lies in the holistic development of individual character and morals. Al-Farabi emphasized the formation of insan kamil, namely perfect humans with good morals and intellectual knowledge that are applied in everyday life. Likewise, the Merdeka Curriculum emphasizes the formation of students with Pancasila character, with faith, noble morals, as well as the development of creativity, taste and initiative. These two approaches are also relevant to the social and national context, where education aims to form individuals who can contribute positively to society and respond to global changes and national interests. Both Al-Farabi and the Merdeka Curriculum see education as a path to perfection in life, which not only includes intellectual aspects, but also spiritual and moral aspects, reflecting the values ​​that must be applied in everyday life.